2013
DOI: 10.3846/20296991.2013.840356
|View full text |Cite
|
Sign up to set email alerts
|

Some Issues Regarding the Calibration of the Terrestrial Laser Scanner Leica Scanstation C10

Abstract: Abstract. Some issues regarding the calibration results pertaining to the ground-based laser scanner Leica Scanstation C10 are presented and analysed. The calibration was carried out at Kyviškės Calibration Baseline (Jokela et al. 2002) and the special cyclic error detection baseline at the Research Institute of Geodesy of Vilnius Gediminas Technical University. The instrument was calibrated at 20, 100, 180, 200 and 260 m distances at Kyviškės Calibration Baseline and the indoors baseline from 1 to 15 m with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The simplification of the procedures is needed as more as the buildings have a remarkable extension and complex shapes. To ensure the reliability of the measurement data, the calibration of the measurement systems is a necessary preliminary step [24]- [27].…”
Section: Test Case Peculiaritiesmentioning
confidence: 99%
“…The simplification of the procedures is needed as more as the buildings have a remarkable extension and complex shapes. To ensure the reliability of the measurement data, the calibration of the measurement systems is a necessary preliminary step [24]- [27].…”
Section: Test Case Peculiaritiesmentioning
confidence: 99%
“…TLS point-cloud TLS 3D point-cloud was obtained using a Leica ScanStation C10, a short-range time of flight TLS with a 360° (horizontally) x 270° (vertically) field of view (FoV), a maximum scanning speed up to 50,000 points per second and characterised by high positional accuracy. For distances up to 100 m, the systematic error of C10 does not exceed 3.7 mm (Antanavičiūtė et al, 2013). C10 uses a green pulsed laser (532 nm of wavelength) for point coordinates detection and an integrated 4-megapixel RGB camera to acquire colour information for each point.…”
Section: Data Collectionmentioning
confidence: 99%
“…Several studies e.g. Abbas et al (2013) and Antanavičiūtė et al (2013) have investigated the calibration parameters of laser scanners Leica ScanStation C10. The results of the studies revealed only minor systematic errors in range measurement and in both horizontal and vertical angle measurement.…”
Section: Deformation Monitoring Using a Tlsmentioning
confidence: 99%